Penegakan Hukum Terhadap Tindak Pidana Penggelapan Dalam Jabatan General Manager PT. Mitsi Citra Mandiri (Analisis Putusan Pengadilan Negeri Medan Nomor : 2662/Pid.B/2017/Pn.Mdn) - Eduard Pakpahan (Iuris Studia: Jurnal Kajian Hukum, 2020)
The problem in this research is how the legal rules regarding the crime of embezzlement, the factors that encourage the crime of embezzlement and how to enforce the law against embezzlement in the General Manager position of PT. Mitsi Citra Mandiri (Analysis of Medan District Court Decision No. 2662 / Pid.B / 2017 / PN.Mdn). This research is an empirical legal research conducted with field research methods and library research using primary data and secondary data as the main raw materials consisting of primary legal materials and secondary and tertiary legal materials which related to the problem. Based on the results of the research, it is known that the rules of the criminal act of embezzlement have been regulated in articles 372, 373, 374, 375 and 377 of the Criminal Code. The factors that led to the crime of embezzlement in PT. Citra Mandiri's myths are: economic factors, excessive trust, poor administration, weak internal control systems, bad organizational culture, technological developments, weak law enforcement, often difficult to distinguish private property from other people's property, disputes, as well as minor criminal threats so as to encourage malicious intent. Law enforcement against the accused of embezzlement in a position as stated in the Medan District Court Decision No. 2662 / Pid.B / 2017 / PN.Mdn was not carried out explicitly, either by the public prosecutor or by the panel of judges who examined the case with a judge's decision acquitting the defendant from all legal charges